Identification of Candidate Coding Region Single Nucleotide Polymorphisms in 165 Human Genes Using Assembled Expressed Sequence Tags - Garg, Kavita; Green, Philip; Nickerson, Deborah A. (Genome Research, 1999)
Using assembled expressed sequence tags (ESTs) from 50 different cDNA libraries, we have identified contigs that represent the complete coding sequences of 850 known human genes, and have scanned these for high quality sequence substitutions. We report the identification and characteristics of 201 candidate single nucleotide polymorphisms found in the coding sequences (cSNPs) of 165 of these genes. Using a conservative calculation, coding region nucleotide diversity (the average number of differences between any pair of chromosomes) was found to be 3 per 10,000 bp based on this data. This analysis reveals that assembled ESTs from multiple libraries may provide a rich source of comparative sequences to search for cSNPs in the human genome.